Incidence of and Risk Factors for Do-Not-Resuscitate Orders in Critically Ill Children: Insights From a Tertiary Care Center in Saudi Arabia - Tareq Alayed; Waad Al-Sowat; Abdullah Alturki; Fahad Aljofan; Moath Alabdulsalam; Tariq Alofisan; Raghad Alhuthil; Munirah Alshalawi; Mansour Alghamdi (Critical Care Research and Practice, 2025)
Conclusions: This study revealed a DNR order rate of 6.4% among all PICU admissions, with 69.2% of PICU deaths occurring in patients with DNR status. Further analysis is warranted to understand the factors influencing DNR decisions and their impact on patient outcomes.